2019
DOI: 10.1039/c8dt04393k
|View full text |Cite
|
Sign up to set email alerts
|

Three viologen-derived Zn-organic materials: photochromism, photomodulated fluorescence, and inkless and erasable prints

Abstract: Three zinc–viologen materials exhibit reversible photochromism, photomodulated fluorescence and the capability as inkless and erasable print media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 39 publications
2
47
1
Order By: Relevance
“…In view of the good photoluminescent properties of Zn (II)‐based CPs, herein, the luminescent properties of nine polymers, free L1 and L2 ligands, as well as four organic dicarboxylic acids were carried out in solid state at room temperature. As shown in Figure , the free L1, L2 ligands, m ‐H 2 BDC and p ‐H 2 BDC molecules exhibit emission maximum at 395, 380, 382 and 393 nm upon excitation at 335, 328, 340 and 346 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the good photoluminescent properties of Zn (II)‐based CPs, herein, the luminescent properties of nine polymers, free L1 and L2 ligands, as well as four organic dicarboxylic acids were carried out in solid state at room temperature. As shown in Figure , the free L1, L2 ligands, m ‐H 2 BDC and p ‐H 2 BDC molecules exhibit emission maximum at 395, 380, 382 and 393 nm upon excitation at 335, 328, 340 and 346 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These potential properties are beneficial to form novel CPs with various topologies. Meanwhile, the unique d 10 configuration of Zn (II) cation enables the Zn (II)‐based CPs to exhibit excellent properties, such as luminescence . In view of the coordination spheres of Zn (II) cation, how to modulate the topological structures and properties through ligand design is particularly important for constructing target CPs.…”
Section: Introductionmentioning
confidence: 99%
“…S8 †). [36][37][38][39][40] The diverse machinability indicated that NEU20 could be used as a portable UV detector and could be applied as an inkless and erasable printing medium.…”
Section: Machinabilitymentioning
confidence: 99%
“…Chromic materials, whose colors change in response to external stimuli such as light, electricity, heat, and chemical species, [1–10] are of great current interest due to their practical applications in various fields. Among various organic chromic materials, substituted 4,4’‐bipyridinium derivatives (viologens) are particularly attractive because of their excellent redox properties, their stabilities, and their highly adjustable geometric structures, which enable the synthesis of the viologen‐derived ligands and the preparation of viologen‐derived metal‐organic materials [11–21] . In the past decade, many viologen‐derived crystalline materials have been synthesized, and a considerable number of them demonstrate fascinating chromic properties [11–23] .…”
Section: Introductionmentioning
confidence: 99%